2021
DOI: 10.1371/journal.pone.0249856
|View full text |Cite
|
Sign up to set email alerts
|

Predicting eyes at risk for rapid glaucoma progression based on an initial visual field test using machine learning

Abstract: Objective To assess whether machine learning algorithms (MLA) can predict eyes that will undergo rapid glaucoma progression based on an initial visual field (VF) test. Design Retrospective analysis of longitudinal data. Subjects 175,786 VFs (22,925 initial VFs) from 14,217 patients who completed ≥5 reliable VFs at academic glaucoma centers were included. Methods Summary measures and reliability metrics from the initial VF and age were used to train MLA designed to predict the likelihood of rapid progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…The model's AUC of 0.66 showed that the study variables contribute to LER prediction, but that other variables are involved as well [ Figure 1a ]. Previous ML studies predicting outcomes in ophthalmic diseases have achieved AUC ranging from 0.68 to 0.79,[ 10 11 21 ] while higher performance has been achieved with large datasets and/or deep learning approaches. [ 7 12 16 ] The present study is remarkable in achieving moderate performance with only a limited number of baseline features.…”
Section: Discussionmentioning
confidence: 99%
“…The model's AUC of 0.66 showed that the study variables contribute to LER prediction, but that other variables are involved as well [ Figure 1a ]. Previous ML studies predicting outcomes in ophthalmic diseases have achieved AUC ranging from 0.68 to 0.79,[ 10 11 21 ] while higher performance has been achieved with large datasets and/or deep learning approaches. [ 7 12 16 ] The present study is remarkable in achieving moderate performance with only a limited number of baseline features.…”
Section: Discussionmentioning
confidence: 99%
“…Visual field measurement is a low-cost diagnostic tool for evaluating visual function. By using a deep neural network trained on low dimensional, baseline 2D visual field measurements, recent studies showed promising predictive power in forecasting the risk of rapid glaucomatous progression ( 12 , 13 ). On the other hand, OCT may be capable of predicting visual field progression ( 14 ).…”
Section: Areas Of Research Opportunities For Reverse Translation Of A...mentioning
confidence: 99%
“…In a retrospective cohort, Shuldiner et al evaluated the ability of different MLCs to detect fast visual field progressors (MD reduction > 1 dB/year). 29 They included a total of 175,786 SAP exams (22,925 initial ones) from 14,217 patients who completed 5 reliable visual fields. Among the MLCs, the support vector machine model (AUC 0.72) presented the highest accuracy to predict progression.…”
Section: Recent Studiesmentioning
confidence: 99%